Trendy sekularne w rozwoju fizycznym i sprawności motorycznej chłopców w wieku szkolnym ze środkowo-wschodniego regionu Polski w latach 1986-2016 = Secular trends in the physical development and motor fitness in schoolboys from central-eastern Poland between 1986 and 2016 - Wilczewski, Robert; Wilczewski, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to assess changes in the physical development and fitness in boys from central-eastern Poland. The studies were conducted in 2015 and 2016 and involved 4995 boys aged 7-18. The obtained data were compared with the results of the studies con-ducted in 1985 and 1986 and with national averages. On the basis of the comparison, the authors revealed the secular trend in body height by 5.26 cm (1.88 cm per decade) and in body mass by 6.36 kg (2.12 kg per decade), and a significant decrease in the level of motor skills (the International Physical Fitness Test). The authors worry about the observable decrease in physical fitness, especially in the youngest age groups (ages 7-13), and its deterioration compared to other peers in various regions of Poland.
Keywords: trend sekularny; chłopcy; rozwój fizyczny; sprawność fizyczna; Międzynarodowy Test Sprawności Fizycznej; secular trends; boys; physical development; physical fitness; International Physical Fitness Test (IPFT)